FAKTOR DETERMINAN HASIL PEMBELAJARAN DARING MAHASISWA: PERAN MOTIVASI INTRINSIK, MOTIVASI EKSTRINSIK, DAN REGULASI DIRI - Eka Ary Wibawa; Rizki Oktavianto; Joni Susilowibowo (Jurnal Pendidikan Ilmu Sosial, 2022)
Student motivation and self-regulation are critical for optimizing online learning outcomes. This study aims to determine the effect of intrinsic motivation, extrinsic motivation, and self-regulation on students' online learning outcomes. This research design is comparative causal research using a quantitative approach. The population in this study was 3,414 students with a sample of 358 students. Data collection techniques and instruments used questionnaires. The validity of the instrument was proved by exploratory factor analysis, while the reliability estimated by using the Alpha formula. Multiple regression analysis was performed to test the research hypothesis. The results showed a positive and significant effect of intrinsic motivation, extrinsic motivation, and self-regulation on students' online learning outcomes. To get the most out of online learning, every student must improve their learning motivation and self-regulation skills.